The Effect Of Internal Audit On The Liquidity Risk Of The General Commercial Banks Operating In Lattakia Governorate (Latakia University Journal - Economic and Legal Sciences Series, 2020)
This study aimed to determine the impact of internal audit through (scientific qualification, independence of the internal audit department, planning the audit process, professionalism) on liquidity risks in public commercial banks in Lattakia Governorate.The researcher followed the descriptive and analytical approach in her study, and a set of methods, including relying on secondary and primary data through a questionnaire that was designed, and distributed to (327) respondents, from which (321) were retrieved, and (319) questionnaires were suitable for analysis, and the research community was made up of a cadre Workers in the branches of public commercial banks in Lattakia governorate (branch manager, department heads, divisional heads, and employees). Then, the SPSS Ver.20 program and a set of statistical analysis tools were used to analyze the available data.The study concluded that there is a statistically significant relationship between the internal audit of the liquidity risks of the public commercial banks operating in the Lattakia governorate, and the existence of a statistically significant relationship between the professional competence and the liquidity risks of the general commercial banks operating in the Lattakia governorate.